Translation of culture in healthcare - Stanojević, Mateusz-Milan (Array, 2003)
In its effort to join the European Union, Croatia faces many challenges in meeting the requirements set by the European policy-makers. Not least of these is the reform of the existing healthcare system, with the pilot of the newly proposed system currently under way in the Koprivnica-Križevci County. The consultants employed by the Ministry of Health in this project being from the United Kingdom, and the planned system being based on concepts largely foreign to the local healthcare professionals, it is obvious that culture presents an essential element of translation and interpretation “ on-the-ground” . On the basis of three English examples of healthcarese expressions and their translations into the Croatian variety of healthcarese, this paper will attempt to show that the prototypical conceptualization of the healthcare process (at least relating to the scope of the examples) is different in the two cultures. The meeting of the two cultures raises two pressing issues: the translators’ awareness of the implicit cultural terms, and, more importantly, the ethics of changing cultural perceptions ; both crucial in the upcoming process of joining the European Union.